2016
DOI: 10.1093/hmg/ddw057
|View full text |Cite
|
Sign up to set email alerts
|

Germline ESR2 mutation predisposes to medullary thyroid carcinoma and causes up-regulation of RET expression

Abstract: Familial medullary thyroid cancer (MTC) and its precursor, C cell hyperplasia (CCH), is associated with germline RET mutations causing multiple endocrine neoplasia type 2. However, some rare families with apparent MTC/CCH predisposition do not have a detectable RET mutation. To identify novel MTC/CCH predisposition genes we undertook exome resequencing studies in a family with apparent predisposition to MTC/CCH and no identifiable RET mutation. We identified a novel ESR2 frameshift mutation, c.948delT, which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…39 However, exome sequencing on a patient with MTC and no identifiable RET mutation has identified a germline frameshift c.948delT mutation in the ESR2 gene. 40 This mutation was also present in 3 family members with C-cell hyperplasia, and immunohistochemical studies confirmed its effect being the loss of ERβ and overexpression of RET. This finding of indirect up-regulation of RET expression leading to MTC provides an interesting insight into alternate pathways for developing MTC, although it has yet to be replicated by other researchers, and its role in sMTC is as yet unknown.…”
Section: Other Genetic Pathwaysmentioning
confidence: 80%
“…39 However, exome sequencing on a patient with MTC and no identifiable RET mutation has identified a germline frameshift c.948delT mutation in the ESR2 gene. 40 This mutation was also present in 3 family members with C-cell hyperplasia, and immunohistochemical studies confirmed its effect being the loss of ERβ and overexpression of RET. This finding of indirect up-regulation of RET expression leading to MTC provides an interesting insight into alternate pathways for developing MTC, although it has yet to be replicated by other researchers, and its role in sMTC is as yet unknown.…”
Section: Other Genetic Pathwaysmentioning
confidence: 80%
“…It should also be stressed that there are no previous reports of germline MET mutations in hereditary MTC. However, RET‐ negative hereditary MTCs are very rare and the only possible driver of such tumors identified thus far is a germline ESR2 mutation, which has also been documented in only one MTC kindred (Smith et al., ). Our failure to find MET alterations in other additional patients whose familial or sporadic MTCs had no known genetic drivers suggests that MET p.Arg417Gln is likely to be a private variant restricted to the kindred we analyzed.…”
mentioning
confidence: 99%
“…The authors also found MET variants involving the Sema domain in the exomes of three sporadic pheochromocytomas (Toledo et al., ). Of note, there are currently no reports implicating germline ESR2 mutations in pheochromocytomas or any other tumors of neural crest origin (Smith et al., ).…”
mentioning
confidence: 99%
“…[148] Exome sequencing of MTCs associated with MEN2A also identified the expected RET mutations, but also suggested that low frequency mutations such as those found in EIF4G1 may also play a role in MEN2Aassociated tumorigenesis by indirectly altering the RET pathway. [158] A similar study was undertaken by Smith et al [159] in MTCs lacking an identifiable RET mutation. Interestingly, this group found a recurrent mutation in the ESR2 gene which encodes the estrogen receptor beta (ER).…”
Section: Nets -Thyroidmentioning
confidence: 87%
“…The authors propose that this may be a novel mechanism by which the RET gene is regulated in RET mutation-negative familial MTC. [159] Heilmann et al [164] performed genomic profiling of MTC cases during the course of clinical care and in addition to the expected RET mutations, also identified amplifications of CCND1, FGF3, FGF19 and CDKN2A. The authors propose that these may be cooperating driver mutations impacting chemoresistance and disease outcomes.…”
Section: Nets -Thyroidmentioning
confidence: 99%